China Upside Down : Currency, Society, and Ideologies, 1808-1856 - Lin, Manhong (Book collections on Project MUSE., 2006)
Some scholars have noted the role of China's demand for silver in shaping the Western dominance of the modern world. This book discusses the interaction of this demand and the early nineteenth-century Latin American independence movements, changes in the world economy, the resulting disruptions in the Qing dynasty and the transformation from the High Qing to modern China.